PENERAPAN DIVERSI DALAM PENYELESAIAN PERKARA ANAK SEBAGAI UPAYA MENGURANGI BEBAN KERJA SISTEM PERADILAN PIDANA DI WILAYAH HUKUM POLRES BENGKULU - Benget Hasudungan Simatupang; Sudirman Sitepu; Pipi Susanti (Ensiklopedia of Journal, 2022)
The treatment of children as perpetrators of criminal acts should be in accordance with the Convention on the Rights of the Child as ratified by the government of the Republic of Indonesia with Presidential Decree Number 36 of 1990 concerning ratification of the Convention on the Rights of the Child (Convention concerning the Rights of the Child) which strictly regulates the rights of children who have problems and are related to criminal justice. The objectives and rationale of juvenile justice clearly cannot be separated from its main objective, namely to realize child welfare which is basically an integral part of social welfare. . Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Criminal Justice System regulates Restorative Justice and Diversion with the mission to avoid and keep children away from the judicial process so as to avoid stigmatization of children who are in conflict with the law and it is hoped that children can return to the social environment as a whole. reasonable. This research is an empirical normative research that uses primary data, namely interviews and secondary data consisting of primary, secondary and tertiary legal materials. Methods of data collection through literature and interviews, while the data collection tool uses interview guidelines. From the results of the research it is known that cases of children who are dealing with the law must be tried at the Juvenile Court which is within the general court environment. The process of court cases for children since they are arrested, detained and tried, their guidance must be carried out by special officials who understand children's problems. However, before entering the judicial process, law enforcers, families and the community are required to seek a settlement process outside the court line, namely through Diversion based on a Restorative Justice approach at the investigation stage at the Police. There are several obstacles faced by investigators in implementing diversion, including victims or victims' families who still have a paradigm of retaliation against perpetrators so that perpetrators are deterred, legal awareness is still low and it is difficult to bring parties together in a meeting so that a diversion agreement is reached.Keywords: Juvenile Case, Diversion, Criminal Justice System.